2010
DOI: 10.1002/jsfa.3892
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plant polyphenols on lipolysis and biohydrogenation in dried forages at different phenological stages: in vitro study

Abstract: These results showed that lipolysis and biohydrogenation of PUFA could be affected by plant phenols, particularly TP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 44 publications
7
69
0
1
Order By: Relevance
“…The level of n-3 fatty acids in milk of grazing animals depends on their concentration in the diet, and is affected by forages botanical composition, phenological stage, and leafiness and conservation method (Cabiddu et al, 2010), as well as biohydrogenation. For example, leaves of Castanea sativa Mill.…”
Section: Fatty Acids Biohydrogenation In the Rumenmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of n-3 fatty acids in milk of grazing animals depends on their concentration in the diet, and is affected by forages botanical composition, phenological stage, and leafiness and conservation method (Cabiddu et al, 2010), as well as biohydrogenation. For example, leaves of Castanea sativa Mill.…”
Section: Fatty Acids Biohydrogenation In the Rumenmentioning
confidence: 99%
“…Plant lipases are important in biohydrogenation with grazed and conserved forages. Polyphenol oxidases can reduce quinones to phenols, which can then bind to lipases and inhibit lipolysis (Cabiddu et al, 2010). There was a negative association between total phenols and LNA biohydrogenation (Cabiddu et al, 2010).…”
Section: Fatty Acids Biohydrogenation In the Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been used as human food (Felker et al, 2013) and their extracts have been extensively evaluated as a source of nutraceuticals (Bernardi et al, 2010) and pharmaceuticals (Huisamen et al, 2013;Mollashahi et al, 2013). The fruits are also used as animal feed (de Jesus Pereira et al, 2013) which, depending on the colour, may have different effects in the rumen (Cabiddu et al, 2010) because of variation in content of phytochemical compounds (mainly polyphenols) (Parveen et al, 2010)). Incidents of invasion of mesquite species as a result of seed dispersal by livestock (Sawal et al, 2004), wildlife and water have been reported in north-east Ethiopia (Shiferaw et al, 2004), forest riverines of Kenya (Muturi et al, 2013), and savannas and grasslands of Argentina and southwestern USA (Golubov et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanics involved in the effect of different forages on rumen biohydrogenation are not fully understood; however, several modes of action have been suggested including the presence of plant metabolites (Dewhurst et al, 2006). The enzyme polyphenol oxidase, present in red clover, has been attributed to reduce lipolysis in the rumen when present, and by doing so reducing hydrogenation as well (Lee et al, 2008;Cabiddu et al, 2010). In addition, condensed tannins may reduce proteolysis, alter the distribution between individual volatile fatty acids produced in the rumen (Burggraaf et al, 2008) and inhibit the terminal step of hydrogenation, resulting in an accumulation of vaccenic acid (Khiaosa-Ard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%